Exploration of Transformational Leadership Style in Improving Employee Performance in the Creative Industries - C Lewaherilla, Novalien; Rahayu, Muji; Limpo, Lita (Yayasan Pendidikan Belajar Berdikari, 2024)
This study looks at the relationship between transformational leadership style, motivation, and employee performance in the creative business. Data were obtained from respondents who work for various companies in the creative industry utilising quantitative methods such as surveys and statistical analysis. The analysis revealed that the model under consideration had a high level of fit (R-squared = 0.608), implying that the research variables could explain the majority of the variation in employee performance. There is a considerable positive association between transformational leadership style, motivation, and performance (r = 0.674, 0.739, and 0.682, respectively). The T test reveals that both transformational leadership style (T count = 5.964) and motivation (T count = 3.910) have a significant impact on employee performance, with T values exceeding the specified T table value. Furthermore, the F test reveals that all research variables have a significant impact on employee performance (F count = 75.320). Finally, transformative leadership and motivation are critical to increasing employee performance in the creative industry. The findings suggest that motivational leadership development and focusing on transformational leadership style can be successful techniques for improving employee performance in the setting of creative industries.